Ultrafast control of strong light–matter coupling. (22nd January 2018) - Lange, Christoph; Cancellieri, Emiliano; Panna, Dmitry; Whittaker, David M; Steger, Mark; Snoke, David W; Pfeiffer, Loren N; West, Kenneth W; Hayat, Alex
Abstract: We dynamically modulate strong light–matter coupling in a GaAs/AlGaAs microcavity using intense ultrashort laser pulses tuned below the interband exciton energy, which induce a transient Stark shift of the cavity polaritons. For 225-fs pulses, shorter than the cavity Rabi cycle period of 1000 fs, this shift decouples excitons and cavity photons for the duration of the pulse, interrupting the periodic energy exchange between photonic and electronic states. For 1500-fs pulses, longer than the Rabi cycle period, however, the Stark shift does not affect the strong coupling. The two regimes are marked by distinctly different line shapes in ultrafast reflectivity measurements—regardless of the Stark field intensity. The crossover marks the transition from adiabatic to diabatic switching of strong light–matter coupling.